Beginning Apache Struts - Doray, Arnold (Apress, 2012)
Any book is the product of a team effort, and this book is certainly no exception. I’m especially grateful to Kunal Mittal, who besides technically reviewing this book, made many suggestions that significantly improved its readability and utility. I’d like to thank Julie Smith for being the perfect project manager—giving support when needed and making sure that everything ran on schedule with a minimum amount of fuss—and all this through email!